The role of cardiovascular magnetic resonance imaging with T1 and T2 mapping in sudden cardiac death survivors. (14th October 2021) - Gil, K; Tong, M S; Afzal, M; Kahwash, R; Bhatti, S; Addison, D; Varghese, J; Simonetti, O P; Zareba, K M; Rajpal, S
Abstract: Background: Sudden cardiac death (SCD) in the adult population is poorly studied, although determining its etiology is crucial for management and prognosis [1]. Cardiovascular magnetic resonance imaging (CMR) is being increasingly utilized in SCD survivors [1, 2]. The role of late gadolinium enhancement (LGE) imaging in patients with recent SCD and no significant coronary artery disease (CAD) is well established, but there is no data on the additive role of T1 and T2 mapping [1–3]. Purpose: This is a retrospective study to assess the role of CMR including T1 and T2 mapping in SCD survivors. Methods: Between 01/2016 and 12/2019, we retrospectively analyzed patients who underwent CMR on a Siemens Magnetom Avanto 1.5 T scanner within 4 weeks of SCD. CMR protocol included cine imaging, T1 and T2 mapping, and LGE imaging. Native and post-contrast myocardial T1 values were measured within the septum on the mid short axis (SAX) and extracellular volume fraction was calculated using the standard formula. T2 values were measured in six mid segments on the mid SAX map. Additional measurements were performed if long axis T2 maps were available. Clinical data, electrocardiography (ECG), transthoracic echocardiography (TTE), coronary computed tomography angiography (CCTA), and left heart catheterization (LHC) were reviewed from the electronic health record. An ischemic evaluation was performed in 33 (94%) of patients. Results: A total of 35 patients who underwent CMR for SCD were included for analysis (mean age 46.9±14.1 years; 20 (57%) male). SCD etiology was established based on clinical data, ECG, TTE, CCTA, and LHC in 9 (26%) patients. CMR provided the most probable SCD etiology in an additional 20 (57%) patients with T1 and T2 mapping abnormalities seen in 18 (51%) patients. Diagnoses determined by CMR included myocarditis (35%), hypertrophic cardiomyopathy (CMP) (20%), left ventricular non-compaction CMP (15%), dilated CMP (10%), takotsubo CMP (5%), and myocardial infarction with non-obstructive CAD (15%) (Table, Figure). Elevated native T1 was seen in 15 (43%) (mean T1 1069±60 ms; site specific normal <1080 ms), elevated ECV in 16 (46%) (30±7%; site specific normal <29%), and elevated native T2 in 22 (63%) patients (65±10 ms; site specific normal <60 ms). LGE was present in 31 (89%) patients. The etiology of SCD remained unknown in 6 (17%) patients despite extensive testing including CMR. Conclusions: CMR has significant diagnostic and prognostic value in assessing SCD etiology compared to non-CMR based evaluation. Myocarditis is a common underdiagnosed cause of SCD in adult patients well seen in a CMR protocol with T1 and T2 mapping. Myocardial inflammation monitoring in SCD survivors with serial CMRs using T1 and T2 mapping could influence clinical decision making by justifying pharmacotherapy modification and timing of ICD implantation. To conclude, CMR with T1 and T2 mapping provides high diagnostic yield in the investigation of SCD etiology. Funding Acknowledgement: Type of funding sources: None.